The Many Worries of Many Worlds - Qureshi-Hurst, Emily ca. 20./21. Jh. (Zygon, 2023)
Theological engagement with quantum mechanics has been dominated by the Copenhagen interpretation, failing to reflect the fact that philosophers and physicists alike are increasingly moving away from the Copenhagen interpretation in favor of other approaches. One such approach, Hugh Everett's so-called Many Worlds Interpretation (MWI), is being taken increasingly seriously. As the MWI's credibility grows, it is imperative that metaphysicians, theologians, and philosophers of religion engage with its ideas and their implications. This article does just that, setting out some implications of Everettian Quantum Mechanics that are particularly relevant to theism. It argues that taking seriously the radical consequences of the Everett interpretation means facing at least three major worries for theism pertaining to personal identity, the problem of evil, and salvation. The article concludes by calling on theologians and philosophers of religion to address these worries, in order that these matters of religious significance remain both coherent and credible if the MWI turns out to be correct.